2021
DOI: 10.3390/jpm11060445
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Delirium Progression in Elderly Patients via Continuous-Time Markov Multi-State Transition Models

Abstract: Poor recognition of delirium among hospitalized elderlies is a typical challenge for health care professionals. Considering methodological insufficiency for assessing time-varying diseases, a continuous-time Markov multi-state transition model (CTMMTM) was used to investigate delirium evolution in elderly patients. This is a longitudinal observational study performed in September 2016 in an Italian hospital. Change of delirium states was modeled according to the 4AT score. A Cox model (CM) and a CTMMTM were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
1
0
1
Order By: Relevance
“…In our study, we have developed the RF algorithm accounting for all the patient’s records observed from the admission to the end of the study. In literature, age is one of the most predictive variables in delirium onset using MLT, regardless of the kind of algorithm [ 28 , 57 , 59 , 61 ] as also shown in our results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, we have developed the RF algorithm accounting for all the patient’s records observed from the admission to the end of the study. In literature, age is one of the most predictive variables in delirium onset using MLT, regardless of the kind of algorithm [ 28 , 57 , 59 , 61 ] as also shown in our results.…”
Section: Discussionsupporting
confidence: 82%
“…The present results show that MLT can identify complex relationship among data, so in the future it would be interesting to use those techniques to define delirium risk factors instead of traditional approaches. Moreover, it would be important to consider delirium as a “dynamic” condition influenced by different factors that are working in different moments as also theorized by Fan et al [ 60 ] and applied in a recent work of our group [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 11 12 Dentro de estos factores se destaca la alteración cognitiva que es un fuerte factor de riesgo para la aparición de delirio (20%). 13 Factores demográficos: ser mayor de 65 años de edad y ser de género masculino. 14 El bajo nivel educativo también se asocia con el delirio, mientras que la educación superior es protectora.…”
Section: Resultsunclassified